Break-Even Point Industri Rumah Tangga Citra Handycraft Sri Sulastri Di Pamulang, Tangerang Selatan - Ita Nuraeni; Layla Exa Wijayanti; Aisyah Ramadania; Anggita Septiyana Dewi; Sutia Budi (Indonesian Journal of Economics Application (IJEA), 2018)
The purpose of this research is to analyze the breakeven on a handy-craft industry of Ms. Sri Sulastri in Pamulang, South Tangerang city. The design of observational research using the method. The design of the survey method using observational with a descriptive quantitative approach. We use costs and marginal approaches, graphical and mathematical methods to analyze break-even and maximum profit on the industry. The results of the analysis of the breakeven on the industry have exceeded break-even. Further elaborations are discussed in this article.